DIGITIZATION OF SERVICES TO KUTARAJA POLYTECHNIC STUDENTS IN INCREASING STUDENT SATISFACTION WITH THE APPLICATION-BASED FIRST IN-FIRST OUT (FIFO) METHOD - Mirnawati wati; Lisnawati; Rizaldy Khair (SEAN Institute, 2022)
Digitalization today occurs as a result of technological advances that have attracted every aspect of human activity. This is what makes a big difference in life in the world including Indonesia. Starting from industry, manufacturing, tourism, health, to the education sector. Especially during the current Covid-19 pandemic which has lasted for almost 2 years, all work activities are carried out online (in the network) which makes everyone increasingly use technology that can support their daily work. The role of technology is accelerating because all activities must be carried out anywhere, anytime, and everyone has to get used to this technological advancement. Kutaraja Polytechnic (PKR) is one of the leading private campuses in the city of Banda Aceh which also feels the change in technology from the educational aspect. When all activities must be carried out from home, the team must innovate to create easy access for students and lecturers to carry out activities in the academic community. Academic Administration Services are realized digitally by creating LMS (Learning Management System) web services, E-Learning, to the use of the Discord and JIRA Platforms in terms of services. This is done in order to improve and facilitate services to students in learning activities to measuring the level of student service satisfaction. However, the education service system that is currently running before the existence of services utilizing technology often results in errors in solving service problems, one of which is the method of solving the problem. Therefore, with technology, services to students can be handled properly with the First-in First-out (FIFO) method [1]. The purpose of this study is to improve services to students in terms of education whose impact can be on the level of student satisfaction by utilizing technology, namely the discord platform, and JIRA. By taking a quantitative approach, the population of all students of the Office Administration Study Program is 56 people. This study uses primary data sourced from direct observation and satisfaction questionnaires based on the ES-Qual which is limited to 4 dimensions, namely Efficiency, Reliability, Fulfillment, and Privacy) which are distributed to 35 samples. The data will be analyzed quantitatively using multiple linear analysis using the SPSS application.